Drought stress memory of primed seeds and the dynamics and resilient of anthesis quality traits in drought stress rice - Mohd Syahmi Salleh (Kulliyyah of Science, International Islamic University Malaysia, 2020)
Seed priming and breeding for drought tolerant rice could be promoted as a potentially sustainable alternative in alleviating drought stress challenges in rice cultivation. The present study was aimed to: 1) investigate the physiological mechanism and durability of drought stress memory in primed seeds of rice, 2) propose a new term called anthesis quality traits for all interrelated traits involved in the flowering process of rice, 3) determine the effects of re-watering on the dynamics of anthesis quality traits in drought stress rice, 4) study the genetics and physiological basis of resilient anthesis quality traits in drought stress rice, 5) screen for potentially tolerant genotype having resilient anthesis quality traits under severe drought at the heading stage, and 6) ascertain the presence of qDTY2.2 and qDTY12.1 in the identified drought tolerant genotype with resilient anthesis quality traits. To date, scientific information on the physiological mechanism and durability of drought stress memory in primed seeds are scarcely available. Laboratory and pot-trial experiment for two seasons were conducted to fulfil those gaps. Results of the present study indicated the involvement of proline in the recruitment of drought stress memory in primed seeds. The acquired stress memory however was temporary and only effective during germination and early seedling growth stages. Therefore, study towards breeding drought tolerant rice was then conducted. The present study hypothesizes that anthesis quality traits is strongly associated with harvestable grain yield under drought and could be potentially used as a selection criterion in breeding drought tolerant rice. Pot-trial experiments using randomized complete block design (RCBD) were conducted to verify this hypothesis. Briefly, spikelet moisture content at above 80% was required to maintain optimum anthesis process in rice for higher spikelet fertility and grain yield under drought. Two novel genotypes of local landraces namely Jarom Mas and Merah Wangi (1) have been identified having resilient anthesis quality traits under severe drought stress at the heading stage. Those two genotypes can retain their spikelet moisture content at above 80% under severe stress condition. The rate of lipid peroxidation level in those genotypes was significantly lower as compared to susceptible control, IR64 suggesting that they were not under stress condition. The genetics and traits association analysis indicated that anthesis quality traits were highly associated with harvestable grain yield under drought and could be used as a selection criterion due to high inheritance values and potential genetic advance. However, assessing anthesis quality traits during the selection process under field condition could be extremely difficult. Therefore, novel phenotyping assessment based on spikelet moisture content and drying score index has been proposed as a more sensible selection criterion. Moreover, the drought grain yield quantitative trait loci (QTLs) of qDTY12.1 was more superior with significantly lower grain yield reduction under severe stress as compared to qDTY2.2. However, those two qDTYs were not detected in the novel genotypes Jarom Mas and Merah Wangi (1) suggesting that other qDTYs/QTLs might be associated with resilient anthesis quality traits under drought in rice. Further study on the association mapping of qDTYs/QTLs with spikelet moisture content may be conducted to identify closely linked major-effect QTLs for future use in marker-assisted breeding of drought tolerant rice.